PERANCANGAN PUSAT WISATA KULINER DI TEPIAN SUNGAI KAPUAS KOTA PONTIANAK - Sari, Dewi Puspita; Gultom, Bontor Jumaylinda BR; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Culinary is a basic need that is related to the cultural results of society. In an effort to preserve culinary culture, it is necessary to design a culinary tourism center as a recreation area to reflect the characteristics of the city of Pontianak. From a geographical perspective, the city of Pontianak is divided by the Kapuas Riverlandscape city, so it can be realized aspoint of view main. Designing a culinary tourism center by optimizing visual contact that prioritizes the river body as the front porch of the building so as to create public open space to increase community accessibility to the use of water bodies. To realize development that does not damage the environmental conditions of rivers, sustainable development is needed with an environmentally friendly architectural approach. The design is planned to create a healthy space through the selection of building materials and systems applied. Design has three main functions, namely recreational, commercial and service. The results of the design are design products for buildings with dynamic articulated forms to create a recreational atmosphere. The main aim of the design is to create a recreational space to accommodate street vendors and culinary-related facilities with spatial planning on the banks of the Kapuas river, Pontianak City. The building consists of three masses arranged radially to create natural ventilation and lighting that can be oriented to the mass of the building as well as circulation from all directions.